Analysis of Factors Affecting Company Value with Dividend Policy as an Intervening Variable in Companies Listed on IDX80 Indonesia Stock Exchange - Edelheid Yuliana Veren Atanus; Henny A. Manafe; Simon Sia Niha; Stanis Man; Paskalis Seran (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the influence of intellectual capital, good corporate governance , and dividend policy on profitability and firm value, and to examine the role of profitability as a mediating variable in this relationship. The study sample consisted of 42 companies selected using purposive sampling from a total of 80 companies in the population. Data analysis was conducted using SEM-PLS operated by SmartPLS 3.0. The results show that intellectual capital has a positive and significant effect on profitability, while good corporate governance and dividend policy have no positive and insignificant effects on profitability. Furthermore, intellectual capital and dividend policy have a positive and significant effect on firm value, while good corporate governance does not have a positive and significant effect on firm value. Profitability is proven to mediate the effect of intellectual capital on firm value, but does not mediate the effect of good corporate governance and dividend policy on firm value